Источник направленного инфракрасного излучения - Архипов В. А. Владимир Афанасьевич; Борисов Б. В. Борис Владимирович; Гущин А. Н. Александр Николаевич; Кирдяшкин А. И. Александр Иванович; Козлов Е. А. Евгений Александрович; Куриленко Н. И. Николай Ильич; Максимов Ю. М. Юрий Михайлович
опубл. 27.10.13